Early maladaptive schemas are associated with self-injury thoughts and behavior in adolescents - Saarijärvi Pauliina; Salmivalli Christina; Helmi Saija; Karukivi Max (BMC, 2025)
Background
Early maladaptive schemas (EMSs) and self-harm have been firmly linked in adults, but research on these associations in adolescents remains scarce. Additionally, the links between EMSs and functions of self-injury has not been previously studied in this age group. Thus, the aim of the present study was to investigate the associations of EMSs with self-harm thoughts and behavior, as well as with self-harm functions, among adolescents in specialized health care.
Methods
The participants were recruited from first-visit 12-22-year-old adolescent patients entering specialized mental health care or pediatric care. For 118 participants, complete data were available for the Young Schema Questionnaire Short Form 2-Extended (YSQ) when entering care and the Ottawa Self-Injury Inventory Functions scale (OSI-F) one year later. YSQ was used to measure the participants' EMSs and OSI-F their self-harm thoughts and behavior. The associations of EMSs and self-harm were investigated in three groups: no self-harm, self-harm thoughts only, and both self-harm thoughts and behavior. The associations of EMSs with self-injury behavior functions were assessed in four categories: Internal Emotional Regulation, External Emotional Regulation, Social Influence, and Sensation Seeking. Additionally, EMSs' associations with addictive features of self-injury behavior were assessed. The magnitudes of effect sizes of differences between the self-harm groups were evaluated with Cliff's Delta. The associations of EMSs with self-injury functions were analyzed with general linear modeling and with self-injury addictive features using logistic regression.
Results
The differences between the self-harm groups were significant for the majority of the EMSs. The stronger the EMSs were, the more severe the manifestations of self-harm. The effect sizes ranged from small to large depending on the EMS. Considering self-injury functions, Internal Emotional Regulation was associated with Self-Sacrifice EMS (p = 0.021), and External Emotional Regulation both with Abandonment (p = 0.040) and Unrelenting Standards (p = 0.012) EMSs. Being addicted to self-injury was associated with Abandonment (p = 0.043) and Dependence (p = 0.025) EMSs.
Conclusions
The present study shows that significant associations between EMSs and both self-harm thoughts and behavior exist also in adolescents. Stronger EMSs are linked to more severe self-harm. Knowledge of these associations may help to improve the understanding and treatment of adolescents suffering from self-harm.